The Process and Status Quo of China’s Urbanization: From the Perspective of the Five-Year Plans - Zhang, Yue (Advances in Social Sciences Research Journal, 2018)
Urbanization is a process of population concentration. China’s urbanization has gained astonishing achievements in the past decades and has accelerated since the reform and opening policies were introduced by Deng Xiaoping in 1978. It is indisputable that a few questions can be raised about such a marvelous process of urbanization. For example, what is the most significant driving force? What are the challenges for China’s urbanization? To answer these questions, this study elaborates the objectives behind China’s urbanization policy as well as the dynamics of it from the perspective of the Five-Year Plans. More importantly, the challenges for China’s urbanization process were emphasized.